Pengaruh Brand Image dan Brand Equity terhadap Keputusan Pembelian Sari Roti di Kota Medan - Mustika Sabilai; Siti Alhamra Salqaura (Mahesa Research Center, 2025)
This research aims to determine the influence of brand image and brand equity on purchasing decisions for Sari Roti in Medan City. The research method used is a quantitative research method using the SPSS application for data analysis. This research uses non-probability sampling with a purposive sampling technique. The population in this research is Sari Roti consumers in Medan City. This research uses the Lemeshow formula to determine the minimum sample size required in the research. And the resulting sample size was 96 respondents. Data analysis techniques use descriptive statistical analysis and multiple linear regression. The results of the study are as follows: (1) Based on the results of the partial test (t-test) the brand image variable (X1) produces a t value of 2.402> t table of 1.985 with a significance value (Sig) of 0.018 (<0.05). Thus, H1 is accepted, which indicates that brand image has a positive and significant effect on the purchasing decisions of Sari Roti in Medan City. And brand equity (X2) produces a t value of 3.488> t table of 1.985 with a significance value (Sig) of 0.001 (<0.05). Thus, H2 is accepted, which indicates that brand equity has a positive and significant effect on the purchasing decisions of Sari Roti in Medan City. (2) Based on the results of the simultaneous test (F test), the calculated F value is 59.752 > F table 3.094 and the Sig value is 0.000 < 0.05, meaning that brand image (X1) and brand equity (X2) simultaneously have a positive and significant effect on purchasing decisions (Y). Thus, H3 is accepted, indicating that brand image and brand equity simultaneously have a positive and significant effect on the purchasing decisions of Sari Roti in Medan City. (3) Based on the results of the determination coefficient test (?!), the Adjusted R Square value is 0.553 = 55.3%, meaning that the brand image variables (X1) and brand equity (X2) affect purchasing decisions (Y) of 55.3%. While the remaining 44.7% is influenced by other variables not examined in this study